The Effect of Variations Temperature in Expansion Valve on The (COP) Coefficient of Performance from An Air Conditioning Engine Prototype Mini Water Chiller - Arnawa, I Komang Gede; Wiratmaja, I Gede; Nugraha, I Nyoman Pasek (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
This experiment aims was to determine the effect of variations temperature in expantion valve on the (COP)Coefficient Of Performance from an air conditioning engine prototype mini water chiller, the prototype mini water chiller was designed by students in the Mechanical Engineering Education, Undiksha. The method used in this research is experimental method. The testing process was carried out at the Refrigeration Engineering Laboratory in Mechanical Engineering Education, Undiksha. In this experiment, the variation of working temperature inÂ expantion valve is determined from 80C, 110C, 140C, 170C and 200C. The tool used to vary the temperature in expansion valve is a thermoelectric cooler. To calculate the (COP) Coefficient Of Performance from prototype mini water chiller, it is necessary to collect data temperature at every several measurement points at T1, T2, and T4. Then from the data acquisition, data processing is carried out to calculate the (COP) Coefficient Of Performance value. After testing, it was found an effect of variations working temperature in expantion valve on the (COP) Coefficient Of Performance from prototype mini water chiller. The lower working temperature in expantion valve, the (COP) Coefficient Of Performance from an air conditioning engine will increase.